Towards a Distance Learning Strategy for Architectural Design Subjects: Case Study, Department of Architecture, University of Tripoli - Dr. Mariam M. T. Shibub (African Journal of Advanced Pure and Applied Sciences, 2025)
Distance education was officially and suddenly imposed at all educational levels in Libya, especially in university education, in 2020 due to the spread of the COVID-19 virus. The Department of Architecture at the University of Tripoli encountered many challenges during the spread of the coronavirus (2019-2020) due to the specific nature of teaching its subjects, especially architectural design subjects, which require direct contact between all elements of the educational process (professor, students, and scientific material) inside the design studio. The most prominent problem was how to communicate, discuss, and evaluate the architectural projects given during the two semesters (Spring 2020 - Fall 2020-2021). This research paper aims to investigate how distance education can be adopted as a tool for architectural education in Libyan universities. Therefore, the main question was raised: What is the extent of the possibility of adopting distance learning in architecture departments at Libyan universities? To answer this question and others, a descriptive-analytical methodology was adopted to collect information about the history of distance education in architectural education. In addition, the questionnaire tool was used to investigate the opinions of students and professors about distance education and its effectiveness in teaching architectural design subjects, to come up with an effective strategy and recommendations that may help adopt the distance learning method as part of the learning process in architectural education in architecture departments in Libyan universities.